Dielectric ceramic material, preparation method thereof and chip multilayer ceramic capacitor
By introducing bismuth zirconate and cobalt titanate into barium titanate ceramics, an optimized dielectric ceramic material is formed, which solves the problem of insufficient bending strength of barium titanate ceramics, and improves the mechanical properties and maintains the electrical properties of ceramic capacitors.
Patent Information
- Application Number
- CN202411731398.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Barium titanate ceramics have insufficient bending strength in multi-layer sheet ceramic capacitors, which can easily lead to device cracking, and adding additives to improve mechanical properties will damage electrical performance and breakdown field strength.
By introducing bismuth zirconate and cobalt titanate, a dielectric ceramic material is formed, with a molar percentage of 80-98% barium titanate, 1-10% bismuth zirconate and 1-10% cobalt titanate, optimize the crystal structure and lattice, and improve the mechanical and electrical properties of the ceramic.
It significantly improves the bending strength and flexural strength of the multi-layer chip ceramic capacitor, while maintaining excellent electrical performance and meeting the voltage withstand requirements of X7R.
Smart Images

Figure BDA0005160353380000061 
Figure BDA0005160353380000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic ceramic components, and in particular to a dielectric ceramic material, a preparation method thereof and a chip-type multilayer ceramic capacitor. Background Art
[0002] In recent years, electronic products such as laptops, satellite communications, smart phones and wearable devices have developed rapidly. Multilayer ceramic capacitors, as a basic circuit electronic component, have also achieved rapid development accordingly, and the market demand has become increasingly larger.
[0003] Barium titanate, as a widely used matrix material in multilayer ceramic capacitors, is known for its excellent dielectric constant. In the production process of multilayer ceramic capacitors, barium titanate is usually prepared into a slurry in the form of powder, and then made into a diaphragm through a casting process. These diaphragms are then processed through processes such as electrode printing, lamination, pressing and cutting to form a green body with a specific shape and size, and finally converted into ceramics through sintering. At present, there is a common problem with barium titanate ceramics, that is, insufficient bending strength. During the assembly and subsequent application of the device, any bending deformation that may be caused may cause the ceramic body to crack, thereby causing the failure of the multilayer ceramic capacitor product. Although the mechanical properties of barium titanate ceramics can be enhanced by adding certain additives, this practice often comes at the expense of its excellent electrical properties and breakdown field strength.
[0004] Therefore, there is still an urgent need to develop a barium titanate ceramic material that has excellent mechanical properties, electrical properties and high breakdown field strength. Summary of the invention
[0005] The object of the present invention is to provide a dielectric ceramic material which can improve the flexural strength and bending resistance of ceramic electronic components such as multilayer chip ceramic capacitors without affecting the electrical performance.
[0006] A first aspect of the present invention is to provide a dielectric ceramic material, which includes barium titanate, bismuth zirconate and cobalt titanate.
[0007] Furthermore, the dielectric ceramic material includes the following components in molar percentage: 80-98% barium titanate, 1-10% bismuth zirconate and 1-10% cobalt titanate. The introduction of bismuth zirconate can improve the mechanical and electrical properties of barium titanate, but when the addition amount is too much, bismuth zirconate cannot be fully dissolved with barium titanate, resulting in a slight decrease in the mechanical properties of the ceramic dielectric ceramic, and a sharp decrease in the dielectric constant of the multilayer chip ceramic capacitor product. Cobalt titanate has good lattice matching with barium titanate, and can better dissolve bismuth zirconate and barium titanate together, thereby increasing the upper limit of the addition amount of bismuth zirconate. Under the joint action of bismuth zirconate and cobalt titanate, the mechanical and electrical properties of the dielectric ceramic material are greatly improved.
[0008] As a preferred embodiment of the present invention, the dielectric ceramic material comprises the following components in molar percentage: 90-98% barium titanate, 5-10% bismuth zirconate and 5-10% cobalt titanate.
[0009] Furthermore, the particle size D50 of the dielectric ceramic material is 1-500 nm.
[0010] Furthermore, the specific surface area of the dielectric ceramic material is 1.5-12.5 m 2 / g.
[0011] Furthermore, the raw materials of the dielectric ceramic material also include a dispersant, a binder, a plasticizer, and a solvent.
[0012] Furthermore, the mass of the dispersant is 1% to 1.5% of the barium titanate.
[0013] Furthermore, the mass of the adhesive is 6% to 10% of the barium titanate.
[0014] Furthermore, the mass of the plasticizer is 1% to 3% of the barium titanate.
[0015] Furthermore, the mass of the solvent is 75% to 95% of the barium titanate.
[0016] Furthermore, the dispersant, adhesive, plasticizer, and solvent may be made of raw materials commonly used in the art. For example, the dispersant may include at least one of polyacrylamide salt and triethanolamine, the adhesive may include at least one of polyvinyl butyral resin and ethyl cellulose resin, the plasticizer may include at least one of dibutyl phthalate and polyethylene glycol, and the solvent may include at least one of toluene, anhydrous ethanol, butanone, and isopropanol.
[0017] The second aspect of the present invention is to provide a method for preparing a dielectric ceramic material, comprising the following steps: mixing raw materials of the ceramic dielectric material to obtain the ceramic dielectric material.
[0018] Furthermore, the mixing step includes grinding and dispersing steps, and a slurry-like dielectric ceramic material is formed through grinding and dispersing.
[0019] A third aspect of the present invention provides a multilayer ceramic capacitor including a dielectric ceramic layer formed by sintering the above-mentioned dielectric ceramic material.
[0020] Furthermore, the sintering temperature is 1000-1500° C., preferably 1100-1300° C. The sintering time is 2-3 h (such as 2 h, 2.5 h, 3 h, etc.).
[0021] Furthermore, the sintering is carried out in an air atmosphere.
[0022] A fourth aspect of the present invention is to provide a method for preparing a multilayer ceramic capacitor, comprising the following steps:
[0023] Forming the dielectric ceramic material into a film to obtain a dielectric ceramic layer;
[0024] forming an internal electrode layer on a surface of the dielectric ceramic layer;
[0025] The dielectric ceramic layers with inner electrode layers formed on the surfaces are stacked, pressed and sintered to obtain a ceramic chip;
[0026] Electrodes are prepared at both ends of the ceramic chip to obtain a multilayer ceramic capacitor.
[0027] Furthermore, the sintering temperature is 1000-1500° C., preferably 1100-1300° C. The sintering time is 2-3 hours.
[0028] Furthermore, the sintering is carried out in an air atmosphere.
[0029] Furthermore, the sintering step includes a binder removal step, that is, the pressed sample is heat treated to burn and remove the binder, plasticizer, etc. in the dielectric ceramic material. The heat treatment temperature is 250-350°C, and the heat treatment can be performed in the air atmosphere.
[0030] Furthermore, the method for forming the internal electrode layer on the surface of the dielectric ceramic layer can adopt a common method in the art, such as printing the internal electrode slurry on the surface of the ceramic dielectric layer to form the internal electrode layer. The thickness of the internal electrode layer and the internal electrode slurry can be selected according to actual needs.
[0031] Furthermore, the electrodes prepared at both ends of the ceramic chip can be electrodes commonly used in the art, such as silver electrodes or copper electrodes, etc., and their thickness can be selected according to actual needs.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The dielectric ceramic material of the present invention improves the mechanical properties of the barium titanate-based dielectric ceramic material by introducing bismuth zirconate and cobalt titanate. When 1-10 mol % of bismuth zirconate and 1-10 mol % of cobalt titanate are added, the bismuth zirconate and cobalt titanate are solid-dissolved into the barium titanate together, and the crystal structure and lattice of the barium titanate are optimized. As a result, the strength and bending resistance of the multilayer chip ceramic capacitor are improved, and under the synergistic effect of bismuth zirconate and cobalt titanate, the electrical properties of the multilayer chip ceramic capacitor are not affected, and the multilayer chip ceramic capacitor can have excellent withstand voltage performance and meet the requirements of X7R. DETAILED DESCRIPTION
[0034] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0035] Example 1
[0036] The dielectric ceramic material includes the following components in molar percentage: 90% barium titanate, 5% bismuth zirconate and 5% cobalt titanate. The dielectric ceramic material also includes a dispersant polyamide salt accounting for 1% of the mass of the barium titanate, an adhesive PVB accounting for 8% of the mass of the barium titanate, a plasticizer polyethylene glycol accounting for 2% of the mass of the barium titanate, and a solvent (toluene and anhydrous ethanol, m:m=1.0~1.5) accounting for 85% of the mass of the barium titanate.
[0037] Example 2
[0038] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 97% barium titanate, 2% bismuth zirconate and 1% cobalt titanate.
[0039] Example 3
[0040] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 95% barium titanate, 1% bismuth zirconate and 4% cobalt titanate.
[0041] Example 4
[0042] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 84.5% barium titanate, 6.5% bismuth zirconate and 9% cobalt titanate.
[0043] Example 5
[0044] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 91% barium titanate, 7% bismuth zirconate and 2% cobalt titanate.
[0045] Example 6
[0046] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 93% barium titanate, 4% bismuth zirconate and 3% cobalt titanate.
[0047] Example 7
[0048] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 81% barium titanate, 9% bismuth zirconate and 10% cobalt titanate.
[0049] Example 8
[0050] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 83% barium titanate, 10% bismuth zirconate and 7% cobalt titanate.
[0051] Example 9
[0052] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 83.5% barium titanate, 8.5% bismuth zirconate and 8% cobalt titanate.
[0053] Example 10
[0054] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 91% barium titanate, 3% bismuth zirconate and 6% cobalt titanate.
[0055] Embodiment 11
[0056] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 98% barium titanate, 1% bismuth zirconate and 1% cobalt titanate.
[0057] Example 12
[0058] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 89.5% barium titanate, 5% bismuth zirconate and 5.5% cobalt titanate.
[0059] Embodiment 13
[0060] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 85.5% barium titanate, 6% bismuth zirconate and 8.5% cobalt titanate.
[0061] Embodiment 14
[0062] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 81.5% barium titanate, 9% bismuth zirconate and 9.5% cobalt titanate.
[0063] Embodiment 15
[0064] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 80% barium titanate, 10% bismuth zirconate and 10% cobalt titanate.
[0065] Comparative Example 1
[0066] The difference from Example 1 is the content of barium titanate, bismuth zirconate and cobalt titanate. No bismuth zirconate is added, and the specific molar percentage is: 95% barium titanate and 5% cobalt titanate.
[0067] Comparative Example 2
[0068] The difference from Example 1 is the content of barium titanate, bismuth zirconate and cobalt titanate. No cobalt titanate is added, and the specific molar percentage is: 95% barium titanate and 5% bismuth zirconate.
[0069] Comparative Example 3
[0070] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 79% barium titanate, 6% bismuth zirconate and 15% cobalt titanate.
[0071] Comparative Example 4
[0072] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 83% barium titanate, 15% bismuth zirconate and 2% cobalt titanate.
[0073] Comparative Example 5
[0074] The difference from Example 1 lies in the contents of barium titanate, bismuth zirconate and cobalt titanate, specifically, the molar percentages are: 85% barium titanate, 12% bismuth zirconate and 13% cobalt titanate.
[0075] The measurement methods of various physical properties are as follows.
[0076] (1) D50 of dielectric ceramic particles
[0077] The dielectric ceramic particles were dispersed in methanol and measured using a laser diffraction / scattering particle size distribution measuring apparatus (LA-950, manufactured by Horiba, Ltd.).
[0078] (2) Specific surface area
[0079] The measurement is performed using a conventional apparatus (for example, TRISTAR II 320, manufactured by Shimadzu Corporation).
[0080] The results of the physical properties are shown in Table 1.
[0081] Table 1. Physical property test results of dielectric ceramic particles
[0082]
[0083]
[0084] Performance Testing
[0085] The dielectric ceramic materials in the embodiments and comparative examples are applied to prepare a multilayer chip ceramic capacitor, comprising the following steps:
[0086] (1) Add barium titanate, bismuth zirconate, cobalt titanate, a dispersant, a binder, a plasticizer and a solvent into a sand mill, and disperse them through sand milling to form a slurry with good stability.
[0087] (2) The ceramic slurry is cast to form a thin film, which is then dried to obtain a 13 μm thick ceramic dielectric layer.
[0088] (3) A 3 μm thick silver-palladium inner electrode layer is formed on the surface of the ceramic dielectric layer obtained in step (2) by a printing process.
[0089] (4) The ceramic dielectric layers printed with the inner electrodes are stacked and then pressed into a block. After pressing, the blocks are cut into green pieces of a certain size.
[0090] (5) Debinding: The cut green embryos are debinded in an air debinding box at 300°C for 25 hours.
[0091] (6) Sintering: Then sinter at 1150°C for 2 hours in an air atmosphere to obtain a ceramic chip.
[0092] (5) Applying external electrode silver paste on both end surfaces of the ceramic chip and baking it at 900°C to form external metal electrodes;
[0093] The following methods are used to test the various properties of multilayer ceramic capacitors.
[0094] (1) Dielectric constant: The dielectric constant was calculated by using an automatic bridge tester under the following test conditions: voltage 1 V, frequency 1 kHz, temperature 25°C. The capacitance C was measured and the dielectric constant was calculated based on the sample size.
[0095] (2) Bending strength: Tested with a tensile tester, the product is welded on a dedicated PCB board, and a pressure of 1 mm / s is applied to the PCB board in the reverse direction until the capacity change rate of the product is greater than 10%, and the pressing distance (mm) is recorded. The greater the pressing distance, the stronger its bending resistance.
[0096] (3) Flexural strength: The product is fixed on the test bench mold using a tensile tester, and a pressure of 1 mm / s is applied to it using a tensile tester until the product breaks.
[0097] (4) Withstand voltage: A DC voltage with a voltage increase rate of 2 V / s is applied to both ends of the device. When the current value reaches 2 mA, the sample is considered to be broken down, and the breakdown voltage at this time is recorded.
[0098] The test results are shown in Table 2. As can be seen from Table 2, within the required range of the present invention, a multilayer ceramic capacitor having excellent dielectric properties and withstand voltage life can be obtained.
[0099] Table 2. Multilayer Ceramic Capacitor Performance Test Results
[0100] Dielectric constant Bending strength / Kgf Flexural strength / mm Breakdown voltage / KV Example 1 3176 6.2 8.9 3.5 Example 2 2943 5.7 8.2 3.4 Example 3 2826 5.6 7.9 3.4 Example 4 3199 6.5 9.3 3 Example 5 2986 6.5 9.1 3.2 Example 6 2869 5.8 8.6 3.5 Example 7 3210 6.4 9.5 3.4 Example 8 3008 6.8 9 3.1 Example 9 3034 6.6 9.2 3.2 Example 10 2934 5.6 8.3 3.6 Embodiment 11 2813 5.7 7.8 3.4 Example 12 3082 5.9 8.8 3.7 Embodiment 13 3106 6.3 9.3 3.3 Embodiment 14 3125 6.5 9.4 3.7 Embodiment 15 3192 6.7 9.5 3.2 Comparative Example 1 2553 3.5 5.5 2.9 Comparative Example 2 2273 5.4 7.1 1.6 Comparative Example 3 2610 3.9 6.2 3 Comparative Example 4 2334 6 7.2 1.5 Comparative Example 5 1694 6.1 5.7 1.8 Comparative Example 6 3204 6.1 8.9 2.8
[0101] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A dielectric ceramic material, characterized in that: The dielectric ceramic material includes the following components in molar percentage: 80-98% barium titanate, 1-10% bismuth zirconate and 1-10% cobalt titanate.
2. The dielectric ceramic material according to claim 1, characterized in that: The dielectric ceramic material includes the following components in molar percentage: 90-98% barium titanate, 5-10% bismuth zirconate and 5-10% cobalt titanate.
3. The dielectric ceramic material according to claim 1, characterized in that: The particle size D50 of the dielectric ceramic material is 1-500 nm.
4. The dielectric ceramic material according to claim 1, characterized in that: The specific surface area of the dielectric ceramic material is 1.5-12.5 m 2 / g.
5. The method for preparing a dielectric ceramic material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing raw materials of the dielectric ceramic material to obtain the dielectric ceramic material.
6. A chip-type multilayer ceramic capacitor, characterized in that: The dielectric layer thereof comprises the dielectric ceramic material according to any one of claims 1 to 4.
7. A method for preparing a chip-type multilayer ceramic capacitor, characterized in that: The following steps are involved: Forming a dielectric ceramic material according to any one of claims 1 to 4 into a film to obtain a dielectric ceramic layer; forming an internal electrode layer on a surface of the dielectric ceramic layer; A plurality of dielectric ceramic layers with inner electrode layers formed on their surfaces are stacked, pressed and sintered to obtain a ceramic chip; electrodes are prepared at both ends of the ceramic chip to obtain a chip-type multilayer ceramic capacitor.
8. The preparation method according to claim 7, characterized in that: The sintering is performed at 1150° C. for 2 hours in an air atmosphere.
Citation Information
Patent Citations
Dielectric ceramic material for multilayer ceramic capacitor with high temperature insulation performance
CN103553591A
Ceramic dielectric material as well as preparation method and application thereof
CN114133238A
Multilayer ceramic capacitor and its manufacture
JP1996069939A
Multi-layered ceramic capacitor
US4835656A
Dielectric ceramic composition
US4925817A